Pemahaman dan Preferensi Bahasa Masyarakat Indonesia pada Istilah Komputer dan Internet - Alfelia Nugky Permatasari; I Dewa Putu Wijana (Universitas Gadjah Mada, 2018)
Technology, including computers and internet, cannot be separated from Indonesians. At the beginning of computers and internet existence in Indonesia, the government took an initiative to make computers and internet equivalent terms through Presidential Decree No. 2 Year 2001. This aimed to ease Indonesians in using computers and/or internet. This effort then generated “Senarai Padanan Istilah